2015
DOI: 10.1039/c5ra09901c
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Fe3O4 nanoparticles on PEG-functionalized graphene oxide for efficient magnetic imaging and drug delivery

Abstract: a Formation of assembly of Fe3O4 nanoparticles (NPs) onto PEG-functionalized graphene oxide for efficient magnetic Imaging and drug delivery are reported. Nanoscale graphene oxide (GO) was first synthesized and functionalized by branched, biocompatible polyethylene glycol (PEG) to render high aqueous solubility and stability in physiological solutions. Next, the meso-2,3-dimercaptosuccinnic acid-modified Fe3O4 NPs were anchored onto GO sheets via formation of amide bond in the presence of 1-ethyl-3-(3-dimethya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The former involves a previous synthesis of MNPs and their subsequent attachment on graphene surfaces by either covalent or non covalent modification. This approach may also imply a previous chemical functionalization of both materials [ 13 ]. However, the most employed methodology is the in situ deposition of MNPs on graphene material.…”
Section: Preparation Of Gbm-mnp Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…The former involves a previous synthesis of MNPs and their subsequent attachment on graphene surfaces by either covalent or non covalent modification. This approach may also imply a previous chemical functionalization of both materials [ 13 ]. However, the most employed methodology is the in situ deposition of MNPs on graphene material.…”
Section: Preparation Of Gbm-mnp Hybridsmentioning
confidence: 99%
“…However, these nanoparticles tend to aggregate and precipitate inside the body vessels, thus reducing the circulation time in blood and the efficiency as contrast agents for long period imaging. As a solution, graphene-based materials have been employed as a support material to anchor IONPs and enhance the physiological stability of the contrast agent [ 13a , 15a ]. Indeed, it was observed that the aggregation of IONPs on GO surface improved significantly the T 2 relaxivity of the system in comparison to the IONPs alone (Fig.…”
Section: Biomedical Application Of the Magnetic Graphenementioning
confidence: 99%
“…6 For example, Fe 3 O 4 nanoparticles have been researched 7,8 and applied as magnetic resonance imaging (MRI) contrast agents because they can improve r 2 relaxivity. [9][10][11] However, they may aggregate easily owing to their tiny sizes and high surface energy, and cause blockages in blood vessels when they are injected into veins. 12,13 Moreover, the surfaces of commonly used Fe 3 O 4 nanoparticles are hydrophobic 6,12 which is incompatible with the human environment.…”
Section: Introductionmentioning
confidence: 99%
“…Coating with a shell offers many advantages such as it prevents agglomeration and helps with further functionalisation and conjugation to proteins, enzymes, antibodies and anticancer drugs. Iron oxide nanoparticles have been investigated for use in magnetic hyperthermia treatment [20,21,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]55], targeted drug delivery and contrast agents in magnetic resonance imaging (MRI) 34,41,56,62]. The magnetic properties of iron oxide nanoparticles can be improved by doping with magnetically susceptible elements such as manganese (Mn), cobalt (Co) and nickel (Ni) [103] …”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…A lot of literature have focused on iron oxide nanoparticles because of their superior chemical, biological and magnetic properties including chemical stability, non-toxicity, biocompatibility, high saturation magnetisation and high magnetic susceptibility [5][6][7][8]. These properties allow for its use in many biomedical applications; bioimaging 34,41,56,62], hyperthermia [20,21,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]55], drug delivery , cell labelling [26,70] and gene delivery [71][72][73][74][75][76][77]. From our most recent review, it was seen that other magnetic nanomaterials such as Fe-Co, Cu-Ni, Fe-Ni, Co-Fe 2 O 4 and Mn-Fe 2 O 4 , nanoparticles are being investigated for use in bioimaging [78][79][80][81][82][83][84][85][86]…”
Section: Introductionmentioning
confidence: 99%